Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Water Exchange Characteristics of Tidally Influenced Hydrilla Invasion Sites in the Lower Connecticut River - Andrew W. Howell; Benjamin P. Sperry; Jens P. Beets; Michael W. Durham; Jonathan S. Glueckert; Amber E. Riner (Estuaries and Coasts, 2026)
The Lower Connecticut River (CR) is an ecologically and recreationally significant ecosystem within New England, but the river has become increasingly vulnerable to the intrusion of aquatic invasive species (AIS) like hydrilla ( Hydrilla verticillata ). The hydrilla population recently discovered in the Lower CR is genetically unlike former hydrilla clades present in the United States. The specific biological and management components of this unique clade-C hydrilla in comparison to its cohorts remains largely undetermined and the nature of management action to combat the submersed plant within the tidally influenced lotic system further complicates waterway resilience efforts due to high-water exchange. Because of the inherent environmental challenges attributed to lotic environs, the use of aquatic herbicides remains the primary management tool for selective and effective hydrilla control. However, knowledge of the site-specific water exchange processes at infested sites coupled with subspecies- and herbicide-specific concentration-exposure time (CET) requirements are essential for successful plant management. The primary goal of the present studies was to quantify bulk water exchange rates at five representative hydrilla infestation sites within the Lower CR using Rhodamine WT dye (RWT) to mimic prospective herbicide application operations. Dye monitoring indicated distinct variability among study site water exchange rates, with RWT half-lives ranging from 0.35 to 72.36 h following application. Future management efforts deploying herbicide should consider these methods and findings when selecting appropriate herbicide active ingredients and use rates to achieve hydrilla control. While the present water exchange findings offer initial guidance, comparable dye studies will be necessary as management programs target additional hydrilla invasion areas within the river.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Application of a population status model on several recreational lake trout (Salvelinus namaycush) fisheries in Manitoba, Canada - Giulio Navarroli; Bradley E. Howell; Andrew W. R. Klein; Eric J. Mullen; Olivier Morissette; Michael D. Rennie; Caleb T. Hasler (Environmental Biology of Fishes, 2025)

Growth patterns of three Hydrilla verticillata biotypes in the United States - Jens P. Beets; Kara J. Foley; Benjamin P. Sperry; Andrew W. Howell; Robert J. Richardson (Aquatic Botany, 2025)

Seismic hazard and shifting channels: Exploring coseismic river response - Erin McEwan; Timothy Stahl; Rob Langridge; Tim Davies; Andrew Howell; Matthew Wilson (Earth-Science Reviews, 2025)

An analysis and successful benchmarking of the Chapman-Enskog-like (CEL) continuum kinetic closure approach algorithm in NIMROD - Joseph R. Jepson; Chris C. Hegna; Eric D. Held; Carl R. Sovinec; J. Andrew Spencer; Eric C. Howell (Computer Physics Communications, 2025)

Naturally occurring radioactive materials in offshore infrastructure: Understanding formation and characteristics of baryte scale during decommissioning planning - Amy MacIntosh; Daniel T. Oldfield; Dioni I. Cendón; Andrew D. Langendam; Nicholas Howell; Daryl L. Howard; Tom Cresswell (Journal of Hazardous Materials, 2024)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

Widespread bleaching in the One Tree Island lagoon (Southern Great Barrier Reef) during record-breaking temperatures in 2020 - Megan K. B. Nolan; Sebastian Schmidt-Roach; Andrew R. Davis; Manuel Aranda; Emily J. Howells (Environmental Monitoring and Assessment, 2021)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Corals in the hottest reefs in the world exhibit symbiont fidelity not flexibility - Emily J. Howells; Andrew G. Bauman; Grace O. Vaughan; Benjamin C. C. Hume; Christian R. Voolstra; John A. Burt (Molecular Ecology, 2020)
Reef‐building corals are at risk of extinction from ocean warming. While some corals can enhance their thermal limits by associating with dinoflagellate photosymbionts of superior stress tolerance, the extent to which symbiont communities will reorganize under increased warming pressure remains unclear. Here we show that corals in the hottest reefs in the world in the Persian Gulf maintain associations with the same symbionts across 1.5 years despite extreme seasonal warming and acute heat stress (≥35°C). Persian Gulf corals predominantly associated with Cladocopium (clade C) and most also hosted Symbiodinium (clade A) and/or Durusdinium (clade D). This is in contrast to the neighbouring and milder Oman Sea, where corals associated with Durusdinium and only a minority hosted background levels of Cladocopium . During acute heat stress, the higher prevalence of Symbiodinium and Durusdinium in bleached versus nonbleached Persian Gulf corals indicates that genotypes of these background genera did not confer bleaching resistance. Within symbiont genera, the majority of ITS2 rDNA type profiles were unique to their respective coral species, confirming the existence of host‐specific symbiont lineages. Notably, further differentiation among Persian Gulf sites demonstrates that symbiont populations are either isolated or specialized over tens to hundreds of kilometres. Thermal tolerance across coral species was associated with the prevalence of a single ITS2 intragenomic sequence variant (C3gulf), definitive of the Cladocopium thermophilum group. The abundance of C3gulf was highest in bleaching‐resistant corals and at warmer sites, potentially indicating a specific symbiont genotype (or set of genotypes) that may play a role in thermal tolerance that warrants further investigation. Together, our findings indicate that co‐evolution of host–Symbiodiniaceae partnerships favours fidelity rather than flexibility in extreme environments and under future warming.

Predicting development preferences for fishing sites among diverse anglers - Rene X. Valdez; Michael D. Drake; Conner R. Burke; M. Nils Peterson; Christopher Serenari; Andrew Howell (Urban Ecosystems, 2019)

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Population collapse dynamics in Acropora downingi , an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature - Bernhard Riegl; Matthew Johnston; Sam Purkis; Emily Howells; John Burt; Sascha C. C. Steiner; Charles R. C. Sheppard; Andrew Bauman (Global Change Biology, 2018)
As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave‐exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table‐coral species A. downingi , population dynamics corresponding to disturbance regimes was quantified in three transition matrices (lower disturbance pre‐1996; moderate disturbance from 1998 to 2010 and 2013 to 2017, disturbed in 1996/1998, 2010/11/12, 2017). Increased disturbance frequency and severity caused progressive reduction in coral size, cover, and population fecundity. Small size‐classes were bolstered more by partial colony mortality than sexual recruitment. Some large corals had a size refuge and resisted die‐back but were also lost with increasing disturbance. Matrix and biophysical larval flow models suggested one metapopulation. Southern, Arabian, populations could be connected to northern, Iranian, populations but this connectivity was lost under assumptions of pelagic larval duration at rising temperatures shortened to a third. Then, the metapopulation disintegrated into isolated populations. Connectivity required to avoid extinctions increased exponentially with disturbance frequency and correlation of disturbances across the metapopulation. Populations became unsustainable at eight disturbances in 15 years, when even highest theoretical recruitment no longer compensated mortality. This lethal disturbance frequency was 3‐fold that of the moderately disturbed monitoring period and 4‐fold of the preceding low‐disturbance period—suggesting ongoing shortening of the disturbance‐free period. Observed population collapse and environmental changes in the Gulf suggest that A. downingi is heading toward at least functional extinction mainly due to increasingly frequent temperature‐induced mortality events, clearly linked to climate change.

Species-Specific Coral Calcification Responses to the Extreme Environment of the Southern Persian Gulf - Emily J. Howells; Glenn Dunshea; Dain McParland; Grace O. Vaughan; Scott F. Heron; Morgan S. Pratchett; John A. Burt; Andrew G. Bauman (Frontiers in Marine Science, 2018)

Fingernail and toenail clippings as a non-invasive measure of chronic cortisol levels in adult cancer survivors - Andrew D. Frugé; Mallory G. Cases; Carrie R. Howell; Yuko Tsuruta; Kelley Smith-Johnston; Douglas R. Moellering; Wendy Demark-Wahnefried (Cancer Causes & Control, 2018)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Mounting evidence: near‐slope seamounts are faunally indistinct from an adjacent bank - Kerry L. Howell; Sophie L. Mowles; Andrew Foggo (Marine Ecology, 2010)
Seamounts have been described as island habitats harbouring a unique fauna, and as biodiversity hotspots with high rates of endemism. However, recent research suggests that these generalisations are inappropriate and poorly supported, though appropriate on and off seamount comparative data are lacking. This study uses quantitative data derived from video analysis to compare epibenthic megafaunal community composition, diversity and potential species endemism on two seamounts and one bank in the Rockall Trough region of the NE Atlantic. Sample data were standardised for substratum type across all three features and as far as possible for depth and geomorphological variation. The results suggest that under similar environmental conditions, e.g . similar substratum, depth and geomorphology, there is little difference between the communities of the bank and seamounts in the Rockall Trough. Where differences are observed, the ‘guyot’ seamount is as different to the conical seamount as it is to the bank. The seamounts are no more or less diverse than the bank; endemism is low or non‐existent. The results are discussed in the context of the common generalisations made concerning seamount communities and the implications for conservation and management of the deep sea.

Using bomb radiocarbon analyses to validate age and growth estimates for the tiger shark, Galeocerdo cuvier, in the western North Atlantic - Jeff Kneebone; Lisa J. Natanson; Allen H. Andrews; W. Hunt Howell (Marine Biology, 2008)

Adult weight gain and central obesity in women with and without a family history of breast cancer: a case control study - Michelle N. Harvie; Saba Bokhari; Andrew Shenton; Linda Ashcroft; Gareth Evans; Ric Swindell; Anthony Howell (Familial Cancer, 2007)

Arabidopsis mutants with increased organ regeneration in tissue culture are more competent to respond to hormonal signals - Andrew Cary; Shyam J. Uttamchandani; Rafaël Smets; Harry A. Van Onckelen; Stephen H. Howell (Planta, 2001)

The Student Watershed Research Project (SWRP): collecting watershed data for use by resource management agencies - Deborah J. Lev; Stacy L. Renfro; D. Torrey Lindbo; Wes Jarrell; Jane Blair; Steve Andrews; Lin Howell (Urban Ecosystems, 1998)